Biosynthesis of cobalt oxide nanoparticles and their cytotoxicity against cancer cells mouse colon adenocarcinoma cell line - Ali Talib al Alawi; Mohammad Talib al Alawi; Nasim Hayati Roodbari; Ali Es-haghi; Mohammad Mashreghi (Results in Chemistry)
The application of plant extracts for the biosynthesis of cobalt oxide nanoparticles is eco-friendly, more economical, less toxic, and more biocompatible. In this study, we used Rose hip extract to synthesize cobalt oxide nanoparticles (Co3O4 NPs). The biosynthesized cobalt oxide nanoparticles were characterized by FT-IR spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The PXRD and FTIR analyses confirmed the successful synthesis and the characteristic bands of Co3O4 NPs, respectively. The FESEM image showed that the Co3O4 NPs were approximately spherical morphology with a mean size of 90.77 ± 32.35 nm. The EDX analysis showed the elemental composition contains carbon in the formulation of Co3O4 NPs. The results showed that the plant extracts can be used to synthesiz cobalt oxide nanoparticles with good quality at nanoscale sizes. The as-prepared Co3O4 NPs exhibited excellent cell toxicity properties against mouse colon adenocarcinoma cells, indicating that biosynthesized cobalt oxide nanoparticles have potential applications in cancer and nanomedicine.